1973
DOI: 10.1128/jb.116.3.1405-1411.1973
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy of the Carboxysomes (Polyhedral Bodies) of Thiobacillus neapolitanus

Abstract: The carboxysomes of Thiobacillus neapolitanus are shown, by electron microscopy, to consist of a paracrystalline array of 10-nm particles surrounded by a “membrane.” The 10-nm particles have a center hole or depression and have been previously identified as ribulose diphosphate carboxylase. The membrane is a monolayer approximately 3.5-nm thick.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(43 citation statements)
references
References 21 publications
7
36
0
Order By: Relevance
“…Our observations elucidate the size variation of β-carboxysomes in Syn7942 cells grown under distinct environmental conditions ( Figure 6B) and adjustable carbon fixation capacities of carboxysomes that may be closely linked to the protein organization and size of carboxysomes. Variations in the diameter of intact carboxysomes, ranging from 90 to 600 nm, have been also shown in previous studies not only in single species but also among distinct species (Shively et al, 1973;Price and Badger, 1991;Iancu et al, 2007;Liberton et al, 2011), suggesting the adaptation strategies exploited by cyanobacteria for regulating their CO2-fixing machines to survive in diverse niches. It may be related to the environment-sensitive protein-protein interactions that drive protein self-assembly and BMC formation .…”
Section: Discussionsupporting
confidence: 75%
“…Our observations elucidate the size variation of β-carboxysomes in Syn7942 cells grown under distinct environmental conditions ( Figure 6B) and adjustable carbon fixation capacities of carboxysomes that may be closely linked to the protein organization and size of carboxysomes. Variations in the diameter of intact carboxysomes, ranging from 90 to 600 nm, have been also shown in previous studies not only in single species but also among distinct species (Shively et al, 1973;Price and Badger, 1991;Iancu et al, 2007;Liberton et al, 2011), suggesting the adaptation strategies exploited by cyanobacteria for regulating their CO2-fixing machines to survive in diverse niches. It may be related to the environment-sensitive protein-protein interactions that drive protein self-assembly and BMC formation .…”
Section: Discussionsupporting
confidence: 75%
“…Since the carboxysomal shell does not show fracture faces, and the organelles are easily fractured in freeze-etch preparations, it is concluded that the shell does not contain hydrophobic parts like the lipids in cellular membranes. These observations confirm and extend the suggestions made by others that the carboxysomal shell is devoid of lipids [12,13]. Much remains to be learned about the carboxysomal shell glycoproteins affecting semipermeability, however.…”
Section: Figs 4 Andsupporting
confidence: 89%
“…In the electron microscope this shell is visualized as a single dark layer of approx. 350 nm [12]. It was suggested that the carboxysomal shell of T. neapolitanus and that of Nitrobacter agilis is devoid of lipids and would consist of glycoproteins only [12,13].…”
Section: Figs 4 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The sulfur globules of Thiovulum majus and, in some instances, those of Beggiatoa and Chromatium exhibit a boundary monolayer made up of globular protein molecules of molecular weight 13500 Da and a diameter of 2.5 nm (SHIVELY 1974). For carboxysomes of Thiobacillus neupolitanus (SHIVELY et al 1973) it was found that two polypeptides (molecular weights 10000 Da and 15000 Da, respectively) are components of the carboxysome "shell" (CANNON and SHIVELY 1983). The boundary layer of gas vesicles in Thiopediu rosea is made up of protein subunits of molecular weight around 14000 Da.…”
Section: Discussionmentioning
confidence: 99%